The correlation between the transverse rectal diameter and urodynamic findings in children with neurogenic bowel and bladder dysfunction - Milivojevic, Sasa; Zelenovic, Aleksandra; Milin-Lazovic, Jelena; Radojicic, Ognjen; Laketic, Darko; Dasic, Ivana; Milic, Natasa; Radojicic, Zoran (Frontiers in Pediatrics, 2022)
BACKGROUND: To examine the correlation between the transverse rectal diameter and urodynamic findings in children with neurogenic bowel and bladder dysfunction. METHODS: Between 2014 and 2022 we prospectively evaluated 81 consecutive spina bifida children with neurogenic bowel and bladder dysfunction (35 boys and 46 girls, mean age 9.5±3.4 years). All patients underwent echosonographic measurement of transverse rectal diameter and urodynamic studies. RESULTS: We found strong negative correlation between transverse rectal diameter and maximum bladder capacity (r=-0.682, p<0.001) and compliance (r=-0.690, p<0.001). There was also a strong positive correlation between transverse rectal diameter and maximal detrusor pressure (r=0.650, p<0.001), leak point preassure (r=0.793, p<0.001) and PVR (r=0.762, p<0.001). In ROC analysis transverse rectal diameter demonstrated good performance for distinguishing children with upper urinary tract deterioration, with an AUC of 0.857 (95%CI 0.761-0.953). A transverse rectal diameter ≥ 40 mm was 83.3% sensitive and 100% specific for diagnosis of unfavorable urodynamic patterns. CONCLUSIONS: There is a correlation between the transverse rectal diameter and urodynamic findings in children with neurogenic bowel and bladder dysfunction. Ultrasonographically assessed transverse rectal diameter ≥ 40 mm may be used as a risk factor for upper urinary tract deterioration (unfavorable urodynamic findings). We suggest the transverse rectal diameter echosonographic measurement use as an integral part of diagnostic approach in children with neurogenic bowel and bladder dysfunction, as it can help decision-making while waiting for urodynamic testing.